Differences in Demographic and Clinical Characteristics of Patients With Depressive vs. Manic First Episode of Bipolar Disorder - Wang, Zhonggang; Cao, Yuying; Zhu, Yaya; Li, Kunkun; Jiang, Xianfei; Zhuo, Chuanjun; Triplett, Patrick; Li, Jie (Frontiers in Psychiatry, 2021)
Background: Bipolar disorder is a serious mental disease marked by episodes of depression, mania, hypomania, or mixed states. Patients with bipolar disorder may present with different symptoms at first onset. The aim of this study is to compare demographic and clinical variables based on a patient's first episode of bipolar disorder, including risk of recurrence over a 2-year period. Methods: A large cohort (N = 742) of patients with bipolar disorder in China was analyzed. Patients were divided into two groups according to their first episode of bipolar disorder, either depression or mania. Patients in mixed state first episode were classified based on predominant symptoms. Three hundred eighteen patients of the cohort had a first episode of mania and 424 patients had initial symptoms of depression. Demographic and clinical data were collected. All patients were followed up for 24 months. Data on compliance with follow-up appointments and recurrence of symptoms after 6, 12, 18, and 24 months were collected. Clinical characteristics (course of disease, age of onset, psychiatric family history, etc.) were compared between the mania group and depression groups. Results: More patients with bipolar disorder had a first episode of depression than mania (57.14 vs. 42.86%). Compared with the depression group, the mania group had later age of diagnosis of bipolar disorder [(38.64 ± 13.50) vs. (36.34 ± 14.94), P = 0.028], lower education level [(9.37 ± 4.34) vs. (10.17 ± 4.81), P = 0.017] and longer latency between an initial episode of psychiatric symptoms and formal bipolar diagnosis [(10.80 ± 10.76) vs. (8.85 ± 9.90), P = 0.012]. More patients in the mania group were male and without psychotic symptoms (all P < 0.05). In comparison with the mania group, more patients in the depression group were female, with higher frequency of a reported precipitating event before first mood episode (all P < 0.05). Compared with the depression group, the mania group had more recurrences of illness at the end of 12 months (Z =-2.156, P = 0.031), 18 months (Z =-2.192, P = 0.028), and 24 months (Z = −2.364, P = 0.018). Conclusions: In our study, there are a number of differences in demographic and clinical characteristics of patients with different onset syndromes of bipolar disorder. These differences include gender, education level, diagnosis age, the rate of recurrences, and others. These data of a cohort of Chinese patients add to the growing international literature on the relationship between index episode of bipolar disorder and clinical variables and outcomes. These results and further study may allow clinicians to offer patients and families more reliable prognostic information at the onset of disease.